2018
DOI: 10.1002/slct.201702981
|View full text |Cite
|
Sign up to set email alerts
|

Well‐Defined Ruthenium Complex for Acceptorless Alcohol Dehydrogenation in Aqueous Medium

Abstract: Synthesis of a water soluble ruthenium complex bearing PNP‐pincer ligand has been described. The complex in presence of KOBut was found to be efficient catalyst for the acceptorless alcohol dehydrogenation (AAD) in aqueous medium. This selective synthetic protocol transforms secondary alcohols to ketones and primary alcohols to aldehydes without formation of any unwanted side products and produces only hydrogen as the sole by‐product.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…For example, starting from alcohols and amines, it is now possible to selectively obtain amides [221][222][223][224][225], imines [226][227][228], imides [229], polyamides [230], pyrroles [231][232][233][234][235], pyridines [236], pyrazines [237][238][239], pyrimidines [240], hydrazones [241], quinolines [242], or aldimines [243,244]. AAD of alcohols also provide access to clean, efficient routes to carboxylic acids [245][246][247][248], ketones or aldehydes [249][250][251], esters [252][253][254][255][256], acetals [257], alkenes [258], as well as lactones [259][260][261].…”
Section: Figurementioning
confidence: 99%
“…For example, starting from alcohols and amines, it is now possible to selectively obtain amides [221][222][223][224][225], imines [226][227][228], imides [229], polyamides [230], pyrroles [231][232][233][234][235], pyridines [236], pyrazines [237][238][239], pyrimidines [240], hydrazones [241], quinolines [242], or aldimines [243,244]. AAD of alcohols also provide access to clean, efficient routes to carboxylic acids [245][246][247][248], ketones or aldehydes [249][250][251], esters [252][253][254][255][256], acetals [257], alkenes [258], as well as lactones [259][260][261].…”
Section: Figurementioning
confidence: 99%
“…Complexes 1 and 2 were prepared by using the reported procedures in literature. 1,2 Nuclear Magnetic Resonance spectra were recorded using Bruker Advance II 400 MHz NMR spectrometer. Chemical shifts were reported in ppm.…”
Section: General Informationmentioning
confidence: 99%
“…Our earlier results obtained with a PTA-coordinated PNN-Ru complex prompted us to investigate the activity of complex 2 for the oxidation of alcohols in aqueous medium. 7 The catalytic dehydrogenation of 1-phenylethanol (3a) to give acetophenone (4a) in aqueous medium was taken as the model reaction for the optimization of the reaction conditions (Table 1). Initially, 5 mol% of the catalyst was tested for the oxidation of 3a in the absence of base with water as the solvent under reflux conditions, and it was observed that the catalyst system was inefficient under these conditions for 24 or 48 hours (Table 1, entry 1).…”
Section: Scheme 1 Synthesis Of Ruthenium Complexmentioning
confidence: 99%
“…6 Recently, our group reported the first example of a ruthenium-mediated conversion of alcohols into the corresponding carbonyl compounds by using a Ru-PNP pincer complex in aqueous medium. 7 Water-soluble phosphines have been used to impart water solubility to transition-metal catalysts. 8 Apart from several ionic water-soluble phosphines, a few nonionic watersoluble cage-like phosphines are also known to induce water solubility in metal complexes.…”
mentioning
confidence: 99%